A Structural Analysis of the Relationship between TQM Practices and Product Innovation - Lee, Voon Hsien; Ooi, Keng Boon; Tan, Boon In; Chong, Alain Yee Loong (Taylor & Francis Group, 2010)
The purpose of this paper is to examine the relationship between total quality management (TQM) practices and product innovation performance as perceived by managers in electrical and electronics (E&E) organizations in Malaysia. This study is based on empirical data collected from a survey of 125 managers of E&E firms. Structural equation modeling analysis is conducted to test the research questions presented in this paper. Results reveal that leadership, strategic planning, customer focus, information and analysis, human resource management, and process management are positively associated with product innovation performance. Information and analysis is perceived as a dominant TQM practice in improving firm’s performance on product innovation. This analysis is especially vital for senior managers of E&E companies who want to establish innovation capability. Senior managers can focus their efforts on TQM practices as means of maximizing organizational gains via product innovation in the context of a competitive environment.